The Effectiveness of Flipped Classroom Models in Undergraduate Medical Education: A Systematic Review: Flipped Classroom Models in Undergraduate Medical Education - Ehsan, Muhammad Tauqeer; Mahrukh, .; Ali, Azqa; Hashmi, Muhammad Suleman Sadiq; Baig, Muhammad Zeeshan; Khan, Fatima Muhammad (Pakistan Journal of Health Sciences, 2025)
The flipped classroom has emerged as a progressive pedagogical model in undergraduate medical education, aiming to improve learning outcomes by combining self-directed pre-class learning with interactive in-class activities. Unlike traditional lectures, this method fosters active engagement, critical thinking, and practical skill development. Objectives: To evaluate the effectiveness of flipped classroom models in improving academic outcomes, student satisfaction, and skill acquisition among undergraduate medical students. Methods: A comprehensive literature search was conducted across PubMed, Springer Link, Science Direct, BMC, Wiley Online Library, and Taylor & Francis for studies published between January 2019 and August 2024. Eligible studies included undergraduate medical or allied health students exposed to flipped classroom models, with outcomes compared against traditional teaching methods. Data extraction and quality appraisal were performed using standardized tools, and results were synthesized narratively due to heterogeneity. Results: Most included studies reported improvements in academic performance, student satisfaction, and engagement. The flipped classroom was particularly effective in enhancing clinical reasoning and knowledge retention. However, some studies demonstrated variable outcomes depending on the quality of implementation and learner readiness. Conclusions: The flipped classroom approach shows considerable potential to strengthen undergraduate medical education. Its effectiveness is maximized when supported by structured implementation, faculty training, and strategies that foster self-regulated learning among students.